Descriptive Evaluative Study – The Use Of Artificial Intelligence Features Reflected On The Performance Of The Company's Employees - Budi Winarno; Hwihanus Hwihanus (Cita konsultindo, 2023)
Artificial Intelligence (AI) provide a significant impact on technological progress, increase performance in various sectors, and improve the quality of human resources. Artificial Intelligence (AI) has been applied to various fields to facilitate human activities such as study and work. This study aims to evaluate existing studies related to the use of AI features associated with daily activities in several fields and formulate directions for further studies that must be carried out from the evaluation of the literature. This study uses a systematic review method on case study journals with keywords “Voice Assistant, Virtual Mentor, Smart Content, Presentation Translator” obtained through the Google Scholar database with a range of 2021 – 2023. Based on the researcher's search, there were 6 journals according to the criteria which were then evaluated based on the parameters Voice Assistant, Virtual Mentor, Smart Content, Presentation Translator from case studies of the use of Artificial Intelligence (AI) in everyday human activities. The results of a systematic review show the use of Artificial Intelligence (AI) features Voice Assistant, Virtual Mentor, Smart Content, Presentation Translator mostly used in education. The use of these features is proven to have a positive effect on teaching and learning activities. Most of the use of Artificial Intelligence (AI) features focuses on application in the education sector, so further research is needed regarding the application of these features to other fields.